RuIII(edta) catalyzed hydrogenation of bicarbonate to formate. Issue 4 (16th February 2016) - Chatterjee, Debabrata; Sarkar, Papiya
Abstract: Selective hydrogenation of bicarbonate to formate catalyzed by a ruthenium(III) complex, [Ru III (edta)] (edta 4−  = ethylenediaminetetraacetate), at moderate H2 pressure (2–8 atm) and temperature (30–40 °C) is reported. Formation of formate, the only reduction product, was identified by 13 C NMR analysis of the resultant reaction mixture. Based on the spectral data, a working mechanism (admittedly speculative) involving the formation of ruthenium(III)-bicarbonate complex, [Ru III (edta)(HCO3 )] 2−, is proposed for the catalytic reaction. Abstract :